2022
DOI: 10.1016/j.cegh.2021.100935
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health awareness and knowledge toward SARS-CoV-2 and COVID-19 vaccines among residents of Makkah, Saudi Arabia

Abstract: Introduction Public awareness regarding COVID-19 plays an important role in controlling the virus’ spread and treating infected people. A high level of awareness among the public will help to implement preventive measures, particularly in the most populated regions, such as Makkah, Saudi Arabia. COVID-19 is an infectious disease and the Saudi Arabian government has taken serious precautions and implemented several preventive measures. In addition, The Ministry of Health (MOH) has launched many awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Overall, the study participants had good knowledge about the COVID-19 vaccine and accepted to take the vaccine, indicating the highly commendable efforts to control the coronavirus. In Saudi Arabia, Alrefaei et al [ 19 ] found that all respondents knew that the coronavirus is contagious, and 89.8% agreed that the symptoms of COVID-19 are similar to those of the seasonal flu. A high level of knowledge of the main factors of SARS-CoV-2 transmission was also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the study participants had good knowledge about the COVID-19 vaccine and accepted to take the vaccine, indicating the highly commendable efforts to control the coronavirus. In Saudi Arabia, Alrefaei et al [ 19 ] found that all respondents knew that the coronavirus is contagious, and 89.8% agreed that the symptoms of COVID-19 are similar to those of the seasonal flu. A high level of knowledge of the main factors of SARS-CoV-2 transmission was also reported.…”
Section: Discussionmentioning
confidence: 99%
“… 831 participants Online questionnaire Awareness of COVID-19ʹs neurological symptoms could help detect an atypical case, which can help in early intervention and its medical treatment. Alrefaei/Jan-Feb 2022 121 Assessment of health awareness and knowledge toward SARS-CoV-2 and COVID-19 vaccines among residents of Makkah, Saudi Arabia. 600 participants Online questionnaire An excellent awareness level was noted among the residents of Makkah for SARS-CoV-2 in terms of transmission, disease symptoms, and prevention of viral spread.…”
Section: The Searched Outcomesmentioning
confidence: 99%
“…These include spreading hashtags and mainstream videos related to the different campaigns which were very useful to the users. A cross-sectional study was conducted in Makkah from February 23 to March 2, 2021, which is the period during the first COVID-19 vaccination awareness campaign [ 29 ]. It showed that the citizens were not aware of COVID-19 vaccination importance and effectiveness as much as they were knowledgeable of COVID-19 infection, symptoms, and prevention strategies.…”
Section: Discussionmentioning
confidence: 99%